KEMAMPUAN MENGARANG BERDASARKAN PENGALAMAN PADA SISWA KELAS V SEMESTER GANJIL SDN 4 JATI BARU LAMPUNG SELATAN - Saputra, Hendra; Rindiantika, Nisdelia; Putri, Tiara Diah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
The problems examined in this study are the Writing Ability Based on Experience in Class V Odd Semester 4 Jati Baru Elementary School South Lampung 2018/2019 Academic Year. The main objects that will be analyzed include: Ideas, organizations, styles, and mechanics. This research was conducted to find out and describe the ability of writing based on the experience of odd grade V students of SDN 4 Jati Baru, South Lampung, 2018/2019 Academic Year. The research method uses descriptive quantitative. The population of this study was 38 classes throughout the class. The study sample was set 38 or the entire population was the subject of research. The sampling technique uses total sampling. Data collection techniques use performance. The data analysis technique uses quantitative descriptive techniques. The results showed that the ability to compile based on the experience in the fifth grade students of the even semester of SD Negri 4 Jati Baru, South Lampung 2018/2019 Academic Year was sufficient, the final average score was 62. Ability in each aspect, namely the ability of students to form aspects of ideas with less the average value is 54, the organizational aspect is lacking because the average value is 55, the aspect of the style reaches an average value of 61 or in sufficient category, the mechanical aspect reaches a value of 74 or enough. Obstacles experienced are less able to determine ideas well because of weak ideas and knowledge, it is difficult to organize ideas because they do not know the technical, there are still many mistakes in words and sentence patterns that vary, also because of lack of understanding, and do not master spelling procedures so that there are many spelling aberrations. The solution starts making a theme or title of the writing, collects the vocabulary according to the theme and selects it, prepares the EYD book for the practice of composing, and continues to compose the essay intensively in the training process.